MENINGKATKAN KONSUMSI OKSIGEN MAKSIMAL DENGAN LATIHAN NAIK TURUN BANGKU BERSELANG DAN KONTINU - Ismaryati Ismaryati; Noor Mukhsin Iskandar; Sujoko Sujoko (PAEDAGOGIA, 2009)
The purposes of this research are to reveal: (1) increasing maximum oxygen consumption through interval and continues step-up training; (2) step up training type that is better to increase maximum oxygen consumption. The research was conducted at Surakarta, using experiment method, with Pre-post Test Control Group Design. The sampleconsistedof60studentstakenrandomly.Thesamplewasdividedintotwogroups. One group was trained with interval step-up, another group with continues step-up. The training was conducted in six weeks and there were three meetings a week. Maximum oxygen consumption data were collected by Multistage Fitness Test. The data were analyzed by T- Test. The results of the data analysis concluded that: (1) the mean of increasing maximum oxygen consumption on interval step-up group was 6.7133 mi/kg body weight, and continues step-up group was 4.0567 mi/kg body weight; (2) interval step-upwasbettertoincreasemaximumoxygenconsumption.